Assessing the environmental impacts of EU consumption at macro-scale. (10th April 2019) - Beylot, Antoine; Secchi, Michela; Cerutti, Alessandro; Merciai, Stefano; Schmidt, Jannick; Sala, Serenella
Abstract: Sustainable Consumption and Production is one of the leading principle towards reducing environmental impacts globally. This study aims at combining Environmentally-Extended Input-Output Analysis (using EXIOBASE 3) with up-to-date impact assessment models to quantify the environmental impacts induced by final consumption in the EU Member States in 2011. The environmental extensions are characterized in 14 environmental impact categories out of the 16 used in the Environmental Footprint life cycle impact assessment method. A contribution analysis of key products and services as well as emissions and resources, which drive the environmental impacts of EU consumption, is conducted. Environmental impacts are mainly induced along the supply-chain of products and services. Several expenditures relative to services represent large shares both in the total final consumption and in the 14 impacts under study, despite a relatively low impact intensity. Food products, in particular meat and dairy products, are identified as key contributors regarding acidification, eutrophication, land use, and water use, and to a lower extent climate change. Finally, several manufactured products, raw materials and basic products respectively importantly contribute to impacts on human toxicity, freshwater ecotoxicity and resource uses. The total volume of final consumption expenditures per EU Member State appears a key explanatory variable to most of the impacts embodied in their consumption, yet to a lower extent regarding water use and fossils resource use. Finally, the current limitations in using EXIOBASE 3 for environmental impact assessment are discussed, with specific attention to EXIOBASE environmental extensions and to the case study on EU consumption. Since the classification of emissions and resources for impact assessment requires a number of assumptions that may influence the results, a sensitivity analysis is performed to exemplify some of the key issues relative to the characterization of impacts based on EXIOBASE environmental extensions. Highlights: Environmental impacts induced by final consumption in EU28 in 2011 are assessed. Environmental extensions are characterized in 14 environmental impact categories following the Environmental Footprint method. Contribution of key products and services and key emissions and resources is analyzed. The total volume of consumption per EU Member State is a key explanatory variable. Current limitations in using EXIOBASE 3 for environmental impact assessment are discussed.